The first Yoruba translation of the Qur’an: a study of Reverend M. S. Cole’s work - Solihu, Abdul Kabir Hussain (2011)
Yoruba (written as Yorùbá in Yoruba orthography) is a large ethno-linguistic group or ethnic nation in West Africa with a population of more than 30 million. The majority of Yoruba live in the southwest of Nigeria. There are also indigenous Yoruba communities in the countries of Benin, Ghana and Togo as well as significant Diaspora Yoruba communities in Brazil, Puerto Rico, and Cuba. Long before the translation of the Qur‘an became acceptable to most Muslims in Africa, Christian missionaries had taken the initiative in rendering the Qur‘an into the local African languages. The first known translation of the Qur‘an into any African language was in the Yoruba language, which was rendered by Bishop Michael Samuel Cole of the Church Missionary Society (C.M.S.). His translation was first published in 1906 and republished in 1924 in Lagos, Nigeria under the title of Al-Kurani ni ede Yoruba. This groundbreaking work undoubtedly set the stage for subsequent translations of the Qur‘an into Yoruba. This paper examines Cole‘s translation of the meaning of the Qur‘an into Yoruba. It will provide an analytical study of selected Qur‘anic verses on historical narratives and theological issues as conceptual terms translated in Cole‘s work. Since Cole relied heavily on English translations, with little, if any, grounding in the Arabic language, the linguistic aspects of the translation and the context in which it was produced will be explored. The primary objective of the paper is to identify the objectives and sources of Cole‘s work.